2016
DOI: 10.1024/0301-1526/a000506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of atherosclerotic lesions by positron emission tomography - can it meet the expectations?

Abstract: Summary:Early non-invasive imaging of atherosclerosis and in particular the detection of lesions at risk with high specifi city could significantly affect cardiovascular morbidity and mortality. Conventional nuclear medicine approaches, in particular using autologous radiolabeled lipoproteins, can be related to histopathological fi ndings; however, they fail to identify lesions at risk. Positron emission tomography (PET) tracers with much better physical properties have been examined, the most detailed informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Intensive statin therapy with atorvastatin at 80 mg daily has also been shown to both improve cardiovascular outcomes and reduce TBR better than lower-dose treatment with atorvastatin at 10 mg daily (Tawakol et al, 2013). Recent advances in the understanding of 18 FDG uptake have shown that the marker is also taken up by endothelial and smooth muscle cells, suggesting that its accumulation is dependent not only on vascular inflammation (Brammen et al, 2016). Studies using 18 FDG PET/CT have shown that vascular inflammation is increased in patients with psoriasis compared with age-and comorbidity-matched control subjects (Mehta et al, 2011;Naik et al, 2015;Rose et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Intensive statin therapy with atorvastatin at 80 mg daily has also been shown to both improve cardiovascular outcomes and reduce TBR better than lower-dose treatment with atorvastatin at 10 mg daily (Tawakol et al, 2013). Recent advances in the understanding of 18 FDG uptake have shown that the marker is also taken up by endothelial and smooth muscle cells, suggesting that its accumulation is dependent not only on vascular inflammation (Brammen et al, 2016). Studies using 18 FDG PET/CT have shown that vascular inflammation is increased in patients with psoriasis compared with age-and comorbidity-matched control subjects (Mehta et al, 2011;Naik et al, 2015;Rose et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[12] Enthusiasm for the clinical use of 18 FDG to identify plaques has diminished over recent years with new tracers such as 18 NaF receiving greater attention; but specific imaging of plaque inflammation is still not available. [13] New, targeted imaging strategies that can identify inflamed plaques in smaller vessels, such as the coronary arteries, with higher specificity are needed.…”
Section: Introductionmentioning
confidence: 99%